From welcome guest to full participant: The influence of migrant worship practices in the Lutheran‐Church Missouri Synod. Issue 3 (8th July 2021) - Marriott, James
Abstract: The Lutheran Church‐Missouri Synod in the United States has a significant, extensive, and winsome history of work with migrant communities. This work includes various parachurch organizations designed for resourcing, social care, and evangelistic witness, aligning with the synodical mission of "Witness, Mercy, and Life Together." Nevertheless, migrant influence on worship practices within LC‐MS congregations can be very minimal. There are a few examples of congregations that have achieved a kind of acculturation or juxtaposition of migrant and local worship practices, and even fewer that are cultivating a kind of inculturation of worship rituals and practices. Using the framework of inculturation and intercultural hermeneutics, this article will seek to highlight the opportunities of congregations within the LC‐MS to cultivate a new sense of worship and community. This new sense of communal worship recognizes the migrant not just as welcome guest but as full participant in "Witness, Mercy, and Life Together, " sharing the stewardship and leadership of rituals, practices, songs, and other ceremonies.